Comparison between national and PAHO criteria for assessing the nutritional profile of foods intended for children aged 0–3 years marketed in Lima, Peru - Aramburu, Adolfo; Chupica-Leon, Jackeline Lizet; Quispe-Quille, Beatriz; Mariaca, Julie; Velarde-Delgado, Patricia; Solis-Sanchez, Gilmer; Morales-Cahuancama, Bladimir; Bravo-Rebatta, Fernando; Ugaz, María Elena; Polo-Campos, Fredy (Frontiers in Nutrition, 2025)
IntroductionThe rising consumption of industrialized infant foods and breastmilk substitutes during early childhood has raised concerns due to their suboptimal nutritional composition, which may contribute to the development of risk factors for non-communicable diseases. This study aimed to assess and compare the nutritional profile of foods intended for children aged 0–3 years marketed in Lima, Peru, using national criteria and the nutrient profile model developed by the Pan American Health Organization (PAHO).MethodsThis cross-sectional, descriptive, and observational study analyzed products purchased from selected supermarkets and pharmacies in metropolitan Lima between September and October 2023. Nutritional labeling information was examined, and the nutritional profile was assessed using the nutrient profile models of Peru (Law No. 30021) and PAHO.ResultsA total of 64 products were analyzed, including 39 breastmilk substitutes, 13 infant cereals, and 12 pureed foods. According to the parameters established by Law No. 30021, 74.5, 1.6, and 37.3% of products were high in total sugars, sodium, and saturated fats, respectively. According to PAHO parameters, the proportion of products classified as high in added sugars, sodium, and saturated fats increased to 83, 6.3, and 41.3%, respectively. Breastmilk substitutes were the main contributors to excessive saturated fat and total sugar content. Additionally, the presence of added sugars was identified in the ingredient lists of 84% of the products, corresponding to 100% of breastmilk substitutes, 53.9% of infant cereals, and 66.7% of pureed foods.ConclusionThe findings indicate that most breastmilk substitutes and foods marketed for children under three years old in metropolitan Lima have an unhealthy nutritional profile. Furthermore, the use of the technical parameters proposed by PAHO allowed for the identification of a higher number of products high in critical nutrients compared to the criteria established by Law No. 30021.